DINAMIKA COLLABORATIVE GOVERNANCE DALAM FESTIVAL LEGU GAM SEBAGAI WISATA KULTURAL KOTA TERNATE - Sumitro S. Syawal; Suleman Samuda (Yogyakarta State University, 2017)
This research aims to know the dynamics of collaborative governance process in implementing Legu Gam as cultural tourism of Ternate City, which the process of collaboration involves multi-stakeholder in accordance with capacity, motivation and extent of involvement starting from planning process and implementation from each stakeholder. Based on the focus, this research used qualitative descriptive approach with data analysis method refers to the interactive analysis model. The results showed that collaboration forum was formed based on Idin Kolano or The decree of the Sultanate Ternate. The value that underlies the Sultanate Ternate in organizing Legu Gam was to preserve adat seatorangin in daylife lifeamid waning of indigenous values and culture of Ternate. Meanwhile by holding Festival of Legu Gam, Ternate municipality government aimed to develop society economy of Ternate city.Keywords: Collaborative Governance , Cultural Tourism, Legu Gam, Ternate City